Working with Smallholders : A Handbook for Firms Building Sustainable Supply Chains - International Finance Corporation (Washington, DC, 2018)
The purpose of Working with Smallholders handbook is to enable the development of more sustainable, resilient and productive supply chains for agribusinesses and to illustrate the substantial development impact.